Primus Inter Pares: Mengungkap Fenomena Praktik Istikharah dan Perhitungan Weton dalam Tradisi Pernikahan Di Lamongan - M. Najib Tsauri (Refleksi: Jurnal Kajian Agama dan Filsafat, 2023)
This article is the result of research that discusses the belief of some Lamongan people in the role of primus inter pares which is considered to have the ability to interpret natural phenomena and human destiny, which is practiced in istikharah and weton calculations in the wedding tradition in Lamongan. This habit can be found in modern society, even today there are still many people who still adhere to this tradition, so it is necessary to respect the diversity of religions and cultures. This phenomenon is an illustration of social religious facts in Lamongan whose existence cannot be denied, thus strengthening the assumption that istikharah and weton calculations have been responded to by Muslims in various practices. For example, asking community leaders or people deemed capable to provide solutions among various social problems. The practice of istikharah and weton calculations basically have the same goal, which is to uncover the truth, even though the two come from different foundations.